Nurse training in health in different regions in Brazil - Carinne Magnago; Celia Regina Pierantoni; Cristiana Leite de Carvalho; Sabado Nicolau Girardi
Abstract Objectives: to identify on the one hand whether there has been any changes in the nurse training in Brazil and on the other if regionalizing health incurred interference in this process. Methods: an exploratory research of a multiple case study in a qualitative approach developed between November 2015 and March 2017, in seven regions in Brazil. The data were collected by in-depth interviews with 16 administrators of the undergraduate courses in nursing and by documentary analysis of the Projetos Políticos Pedagógicos (Political Pedagogical Projects). Content analysis was undertaken by having the theoretical references of the Diretrizes Curriculares Nacionais (National Curriculum Guidelines). Results: varied profiles of undergraduates were observed with higher tendency for the basic level in health practice or for hospital level with competencies in health care that is still fragmented and not interdisciplinary. The curricular structure of the courses focuses on isolated disciplines with little or no interdisciplinary integration and the pedagogical model is based on traditional teaching-learning strategies and additional evaluation process. There were no differences in health among the regions. Conclusions: it is necessary in concomitance with the changes that are required in the field of training to undertake efforts in the development of health units and training institutions, which has already proven to be a factor of professional retention and regional development.